Diagnosis and management of intrahepatic cholestasis of pregnancy- a retrospective clinical audit - Viswanathan, Linggesuwary; Sthaneshwar, Pavai; Razali, Nuguelis; Thambiah, Subashini C. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Pregnant women presenting with pruritus, serum bile acid (SBA) 10 µmol/L and/or alanine transami- nase (ALT) >30 U/l is diagnostic of intrahepatic cholestasis of pregnancy (ICP). A retrospective audit was performed to look at the diagnosis, management and outcomes of ICP patients in University Malaya Medical Center (UMMC). Methods: SBA requests from Obstetrics and Gynaecology Department from 1st January 2016 to 31st December 2020 were extracted from Laboratory Information System (LIS). The medical records (preexisting medical conditions, ma- ternal and perinatal outcomes) of ICP were obtained. Mild and severe ICP were defined based on SBA 10-40µmol/L and SBA >40 µmol/L, respectively. Results: SBA was requested for 202 pregnant women. The prevalence of ICP in our cohort was 0.18% (47 out of 26,697 deliveries). The average gestation at diagnosis was 35 weeks. Both SBA and liver enzymes were elevated in 25 (53.2%) whereas only SBA was elevated in 20 (42.6%) women. In two women, the diagnosis was made based on clinical symptoms and elevated liver enzyme alone. All with ICP had a livebirth and 31.9% were preterm. Severe ICP was noted in eight (17%) and all had cesarean section, whereas, in mild ICP, only 17 (44%) had a caesarean section. In those with normal SBA (n=149) at initial presentation, a repeat SBA was performed only in 12 (8.1%). Postpartum follow-up of ICP patients was observed in only 10 (21.2%). Conclusion: Despite being an uncommon diagnosis in our population, early diagnosis and timely delivery is important to reduce the major perinatal adverse outcomes. In women with persistent pruritus but without the biochemical evidence of ICP at the time of presentation should have repeat SBA and LFT done.